2015
DOI: 10.1080/13552600.2015.1057243
|View full text |Cite
|
Sign up to set email alerts
|

Sexual offenders’ parental and adult attachments and preferences for therapists’ interpersonal qualities

Abstract: This study explored sex offenders' parental and adult attachment difficulties and assessed the extent to which these were associated with preferences for therapists' interpersonal qualities.One-hundred and twelve adult male child sexual offenders were invited to provide self-report data on their attachment histories, adult attachments and preferences for therapists' interpersonal qualities. A weak relationship between childhood and adulthood secure attachment was found, suggesting that attachment at the time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…As previous research emphasizes, the attachment patterns can vary greatly depending on the reference person (Asendorpf, 2018;Caron et al, 2012). Additionally, the clients' attachment styles not only influence the relationship to the therapist but also to the other members of the therapeutic group (Jennings et al, 2021;McKillop et al, 2016;Rom & Mikulincer, 2003;Sonkin & Dutton, 2003). Nevertheless, it is still open to question whether or not the use of the ECR-R is appropriate to capture the relationship to the therapist and other members of the therapeutic group in forensic settings.…”
Section: Perceived Self-efficacy and Adult Attachment Styles -Critica...mentioning
confidence: 99%
See 1 more Smart Citation
“…As previous research emphasizes, the attachment patterns can vary greatly depending on the reference person (Asendorpf, 2018;Caron et al, 2012). Additionally, the clients' attachment styles not only influence the relationship to the therapist but also to the other members of the therapeutic group (Jennings et al, 2021;McKillop et al, 2016;Rom & Mikulincer, 2003;Sonkin & Dutton, 2003). Nevertheless, it is still open to question whether or not the use of the ECR-R is appropriate to capture the relationship to the therapist and other members of the therapeutic group in forensic settings.…”
Section: Perceived Self-efficacy and Adult Attachment Styles -Critica...mentioning
confidence: 99%
“…A meta-analysis involving three studies which compared attachment styles across different types of sexual offenses found that men convicted of child sexual abuse were more anxious in their attachment style, while men convicted of rape were more avoidant (Ogilvie et al, 2014). Therefore, adult attachment styles should be considered more with regard to group treatment programs, given that such groups often include members with various attachment styles, and therefore a range of potential attachment difficulties (Jennings et al, 2021; McKillop et al, 2016; Ogilvie et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To the author's knowledge, there is nothing in the theoretical literature that postulated this relationship directly. In the empirical literature, insecure childhood attachment has been linked to sexual offending in men (McKillop, 2016;Smallbone & Dadds, 1998), also characterized by parents' authoritarian monitoring of their (later sexually offending) boys with lack of warmth (McKillop, 2016). However, meta-analytic findings reveal that a lack of secure attachment to parents has been associated with offending in both boys and girls (Hoeve et al, 2012).…”
Section: Familymentioning
confidence: 99%